The Formation of Abbreviation in the Terminological System of Oil and Gas Industry - Shaymanovich, Xasan Abdinazarov (Researchparks Publishing, 2023)
In the terminological system of oil and gas industry in the English and Uzbek, there are a great number of abbreviations formed. Furthermore, the abbreviations in the terminological system of oil and gas engineering originated from the terminology of oil and gas industry in the English. Some of them is hard to understand if one has no idea about this field of work. Abbreviations are essential to study the terminology in this field of. However, a learner must know the area of expertise to interpret the abbreviation. In each field of study, such as medicine, mathematics, physics, art has its abbreviated words.